2020
DOI: 10.3390/biom10060812
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Drug Design for Purinergic GPCRs: Overview on Molecular Dynamics Applied to Adenosine and P2Y Receptors

Abstract: Molecular modeling has contributed to drug discovery for purinergic GPCRs, including adenosine receptors (ARs) and P2Y receptors (P2YRs). Experimental structures and homology modeling have proven to be useful in understanding and predicting structure activity relationships (SAR) of agonists and antagonists. This review provides an excursus on molecular dynamics (MD) simulations applied to ARs and P2YRs. The binding modes of newly synthesized A1AR- and A3AR-selective nucleoside derivatives, potentially of use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 148 publications
0
19
0
Order By: Relevance
“…While previous review papers have shown how MD simulation has helped elucidate the role the lipid membrane plays in substrate and thus drug selection for membrane proteins [28][29][30][31][32], drug membrane interactions [33][34][35][36][37][38][39][40][41], drug delivery [3,[42][43][44][45], antimicrobial peptides [46][47][48][49][50][51][52][53][54], and methodologies [28,[55][56][57][58][59][60], this is the first review paper, that we are aware of, focusing on the entirety of the use of MD simulation to incorporate the role played by interactions with lipid membranes in drug design. This can be seen, in turn, as a case study of the potential for MD simulation to expand the paradigm of drug design to all aspects of the broader biophysical environment within which drug action occurs.…”
Section: Introductionmentioning
confidence: 95%
“…While previous review papers have shown how MD simulation has helped elucidate the role the lipid membrane plays in substrate and thus drug selection for membrane proteins [28][29][30][31][32], drug membrane interactions [33][34][35][36][37][38][39][40][41], drug delivery [3,[42][43][44][45], antimicrobial peptides [46][47][48][49][50][51][52][53][54], and methodologies [28,[55][56][57][58][59][60], this is the first review paper, that we are aware of, focusing on the entirety of the use of MD simulation to incorporate the role played by interactions with lipid membranes in drug design. This can be seen, in turn, as a case study of the potential for MD simulation to expand the paradigm of drug design to all aspects of the broader biophysical environment within which drug action occurs.…”
Section: Introductionmentioning
confidence: 95%
“…, in a review article, provided a detailed discussion of recent MD studies of purinergic GPCRs, including well-known adenosine receptors and P2Y receptors. 61 This article indicated that enhancement of traditional MD simulations algorithms has enabled researchers to explore more complicated and long-timescale phenomena, including receptor activation, recognition, and dissociation pathways in GPCR biosystems at an atomistic level. Furthermore, Wang et al.…”
Section: Molecular Mechanisms Of Gpcr Structure and Signalingmentioning
confidence: 99%
“…60 Salmaso et al, in a review article, provided a detailed discussion of recent MD studies of purinergic GPCRs, including well-known adenosine receptors and P2Y receptors. 61 This article indicated that enhancement of traditional MD simulations algorithms has enabled researchers to explore more complicated and long-timescale phenomena, including receptor activation, recognition, and dissociation pathways in GPCR biosystems at an atomistic level. Furthermore, Wang et al employed all-atom simulations by a robust Gaussian accelerated molecular dynamics (GaMD) method on adenosine receptors (ARs), including subtypes of A 1 AR and A 2A AR, and deciphered detailed mechanism of specific AR-G protein coupling.…”
Section: Molecular Mechanisms Of Gpcr Structure and Signalingmentioning
confidence: 99%
“…Our primary interest is not the development of P2Y 12 R antagonists, which is highly advanced in the pharmaceutical industry, rather the design of ligands for homologous receptor subtypes. Given the availability of P2Y 12 R X‐ray structures, we were able to derive a homology model of the closely related (45 % sequence identity) hP2Y 14 R and apply that model to ligand design [10] . We had previously introduced numerous P2Y 14 R agonists, and now the availability of a close template for P2Y 14 R homology modeling allows us to both retrospectively analyze agonist binding and to prospectively guide antagonist design.…”
Section: P2y12r Receptor Structures Used To Design New P2y14r Antagonmentioning
confidence: 99%
“…Biophysical methods used to study GPCR structures include X‐ray crystallography, X‐ray free‐electron laser (XFEL), cryogenic electron microscopy (cryo‐EM), and NMR [7] . Also, advances in the computational modeling of membrane‐bound proteins like GPCRs have provided an interface for medicinal chemists to predict the effects of ligand structural changes on the GPCR binding and activation processes [8–10] . The derived theoretical modeling enhances the utility of the crystallographic structures generated toward predictions for novel ligands, beyond the ligands that are present in the X‐ray structures.…”
Section: Introductionmentioning
confidence: 99%